Wavelet Based Analysis of Major Real Estate Markets - YILMAZ, Adil; UNAL, Gazanfer; KARATAS, Cengiz (Journal of Advanced Studies in Finance, 2017)
Wavelet coherence of time series provide valuable information about dynamic correlation and its impact on time scales. Here, we analyze the wavelet coherence of major real estate markets data. Our paper is the first to link co-movement in terms of wavelet coherence. Here we consider USA, Canada, Japan, China and Developed Europe real estate market prices as time series. Wavelet coherence results reveal interconnected relationships between these markets and how these relationships vary in the time-frequency space. These relationships allow us to build VARMA models of real estate data which yield forecast results with small errors.
Keywords: real estate markets; REIT; co-movement; wavelet coherence; VARMA